1983
DOI: 10.1046/j.1468-2982.1983.0304231.x
|View full text |Cite
|
Sign up to set email alerts
|

Total IgE, Specific IgE and Prick-Tests Against Foods in Common Migraine—A Prospective Study

Abstract: A prospective study of total IgE, specific IgE against 12 common foods, and prick-tests with 11 common food allergens was performed on 50 consecutive migraine sufferers. Total IgE levels were found above 100 kU/l for seven patients, but five of them were atopic. Prick-tests and RAST were positive for four and six patients (class 1), respectively. Food challenge on these six patients did not cause any migraine attacks. This study thus indicates a very low frequency of allergic dietary migraine to common foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
1
22
1
2
Order By: Relevance
“…However, in other countries (France, Italy) white wine (in France also champagne) is viewed as the major culprit [5, 6]. In addition, another study reported a surprisingly higher correlation of spirits and sparkling wine to migraine attack, compared to other alcoholic drinks.…”
Section: Is Alcohol Per Se or Another Component Of Alcoholic Drinks Tmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in other countries (France, Italy) white wine (in France also champagne) is viewed as the major culprit [5, 6]. In addition, another study reported a surprisingly higher correlation of spirits and sparkling wine to migraine attack, compared to other alcoholic drinks.…”
Section: Is Alcohol Per Se or Another Component Of Alcoholic Drinks Tmentioning
confidence: 99%
“…However, despite the original paper of Hanington [3] and the vigorous literature that follows, serious doubts exist as to whether the condition really exists as a clinical entity. The commonest initiator of an attack is alcoholic beverages and by far the largest and most notorious is red wine, at least in the United Kingdom [4], while in other countries, white wine (France, Italy) and champagne (France) are viewed as the major culprits [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…This property may be connected (at least in part) to the previously described histamine-releasing factors (HRFs) detected in the plasma of migraine patients. This is indirectly reasserted by the absence of any IgE-dependent histamine release [32] in the investigated patients and by the normal plasma levels of the main HRFs, i.e. IL-3, IL-5, GM-CSF, and MCP1-4 (unpublished results).…”
Section: Discussionmentioning
confidence: 64%
“…Während Migräneattacken im Speziellen wurden erhöhte Histaminkonzentrationen im Plasma bei 27 Patienten beobachtet [47]. Mehrere Studien berichten über teilweise erhöhte Konzentrationen des unspezifischen, gesamten IgE bei Migränepatienten [3,20,70]. Weitere Studien bei Erwachsenen (mit n=6 [74] bis n= 119 [62] fanden keine erhöhten IgE-Spiegel [62,67,74,86].…”
Section: Allergie Und Migräneunclassified